Die Seele im Kosmos: Porphyrios, Über die Nymphengrotte in der Odyssee - Porphyrius; Baumbach, Manuel; Becker, Matthias; Glei, Reinhold; Männlein-Robert, Irmgard; Riedweg, Christoph; Topp, Benjamin (Scripta Antiquitatis Posterioris ad Ethicam REligionemque pertinentia, 2019)
Homer's puzzling description of a cave of nymphs leads Porphyry to a fascinating interpretation setting out the journey of souls in the cosmos, answering questions about their immortality, and providing insights into the intelligible world. Alongside the text and an annotated translation, this volume offers four interpretative essays from different disciplinary perspectives.